Physico-chemical characteristics of a local spice (Zanthoxylum armatum DC) of Arunachal Pradesh and its utilization for development of blended tea - Samyor, Duyi; Bosco, John Don; Cynthia, S J; Bepary, Rejaul Hoque; Mahnot, Nikhil Kumar; Kumar, Krishan; Tsomu, Thupten; Maying, Billin; Tasung, Ampee; Tamut, Omem (Journal of Postharvest Technology, 2022)
Zanthoxylum armatum DC has been used in traditional medicinal systems to cure various health related problems. The essential oil extracted by the hydrodistillation method was further analyzed  for parameters such as iodine value, peroxide value, and the GC-MS volatile compound profile.  Eight blended tea formulations based on yarma spice powder (SBT) and another eight blended  tea formulations using essential oil (EBT) were developed and analyzed for sensory acceptability.  The formula with the highest sensory score formula among the formulae was selected and termed  optimized blended tea based on yarma spice powder (SBTo) and optimized blended tea based  on yarma essential oil (EBTo). The SBTo product was analyzed for color, bulk and tapped density,  moisture, protein, ash content, minerals, total polyphenolic content, and vitamin C, and compared  with existing market tea (EMT). The physico-chemical properties of yarma fruits were as follows:  length - 5.665 mm, width - 4.393 mm, thickness - 4.525 mm, fruit surface area - 48.57 mm2, fruit  volume - 52.327 mm3, bulk density - 0.922 g/ml, true density - 2.305 g/ml, moisture - 10.26 ± 0.64%,  ash - 4.33 ± 0.28%, carbohydrate content - 15.72 ± 0.87 g, protein - 10.06 ± 0.6 g, fat - 0.8 ± 0.4  g. The yield of essential oil was 6.73 ± 0.0057% v/w, and it contained 16 different major volatile  compounds revealed by GC-MS analysis. The acceptability of SBTo was comparable to EMT, and it  contained carbohydrates (21.66 ± 0.28 g), protein (4.71 ± 0.14 g), total phenolic content (92.40 GAE  mg/g), and reducing power assay (37.8 mg/100 g). The yarma spice powder-based blended tea was  rich in essential oil, volatile compounds, and antioxidant activity.
Keywords: Yarma,; Zanthoxylum armatum; essential oil; GC-MS,; blended tea